Rethinking the science–policy interface in South Africa: Experiments in knowledge co-production - Swilling, Mark (South African Journal of Science, 2014)
This article contributes to the increasingly significant discussion about the science–policy interface. The challenge therein is that such a discussion tends to revolve around two seemingly mutually exclusive approaches: the reflexive approach inspired by Maarten Hajer’s work that deconstructs the discourses of participatory policymaking, and the more normative transdisciplinary approaches that legitimise researchers as active change agents. With reference to a discussion of three South African case studies characterised by practical involvement of researchers in change processes, it is concluded that both approaches have merit and can improve the other: the reflexive approach could benefit from a better understanding of appropriate research methods for facilitating authentic engagement and participation, and the transdisciplinary approach could benefit from some reflexive caution about the change agent roles of researchers. The dynamics of the case studies and conclusions are significant in light of the fact that the South African research community is being influenced by re-alignments in the global scientific research community, resulting in an increasing emphasis on the need to do transdisciplinary research. For example, the adoption by some of the most significant global scientific associations in the natural and social sciences of the Future Earth platform at the Rio+20 conference in 2012 reflects most clearly this re-alignment. Researchers would be well advised to critically engage this agenda rather than presume it means little more than a rewording of traditional interdisciplinary approaches.